Consumer Awareness towards Agriculture Equipment - Dr. V.Vinodhini; K.Ruban Raaj; S.Lingesh Waran; K.S. Vasanthbala (International Journal of Engineering and Management Research, 2023)
The Project's motive is to let know awareness among farmers. The project's purpose is for the farmers to let them know the affordable and quality products near shops in suggesting the best sites. The farmers do not need to wander and choose the product, instead of that they will benefit from the website and get the products at the affordable and best rates. Using some software will create this website. Consumer awareness towards agriculture equipment refers to the level of understanding and knowledge that consumers have about the different types of equipment used in agriculture and their applications. This includes knowledge about the various features and benefits of different equipment, as well as any potential drawbacks or limitations. Analyzing consumer awareness towards agriculture equipment can be done by collecting text data such as social media posts, forum discussions, and customer reviews related to agriculture equipment This can help manufacturers and sellers understand what consumers are looking for in agriculture equipment and how they perceive different products. Additionally, analyzing consumer awareness can also help researchers and policymakers identify areas where education and outreach efforts may be needed to improve understanding of the importance and benefits of modern agriculture equipment.